KAEDAH MNEMONIK AKRONIM DALAM MATA PELAJARAN REKA BENTUK DAN TEKNOLOGI DI SEKOLAH RENDAH AGAMA BERSEPADU MERSING - Mohd Jamil, Umi Fairus; Ab Halim, Fazlinda (Online Journal for TVET Practitioners, 2018)
The purpose of this study was to investigate the extent to which the use of the acronym mnemonic method can attract and improve pupils' recollection of the subjects studied in Design and Technology subjects at Mersing Integrated Religious Primary School. This study uses survey method which the sample consists of 86 respondents from different sexes of three age groups; 10, 11 and 12 years. The research instrument includes a set of questionnaire containing 22 items. Statistical Package for The Social Sciences (SPSS) version 22.0 is used to perform statistical analysis. Analysis data includes mean score and percentage. The results showed that the level of students' interest in design and technology subjects through the use of the acronym mnemonic method was high. Meanwhile, the level of pupil’s memory also at a high level through the use of an acronym mnemonic method. This suggests that, this method is practically practiced among primary school students, as it is not only able to attract learning but also to improve the memory of the students to master a topic more quickly.